Microstructural, thermal, and radiation shielding properties of Al50B25Mg25 alloy prepared by mechanical alloying - Yaykaşlı, Hakan; Eskalen, Hasan; Kavun, Yusuf; Gögebakan, Musa (Journal of materials science. Materials in electronics, 2022)
Aluminum, boron, and magnesium are one of the most common aerospace infrastructure materials. Therefore it is important to know their effectiveness in radiation shielding. In this study, Al–B–Mg powder alloy with a nominal composition of Al 50 B 25 Mg 25 was synthesized by using a mechanical alloying (MA) process under an argon gas atmosphere for potential use as a aluminum based engineering material. Microstructural evolution, thermal behaviour, and mechanical properties of the mechanically alloyed powders as a function of milling time were investigated by means of X-ray diffraction (XRD), differential scanning calorimetry, transmittance electron microscopy and scanning electron microscopy (SEM). The XRD and SEM results revealed that the microstructure of the powders materials changed during MA. The crystallite size of Al–B–Mg powders decreased with increasing milling time. The average crystallite size was determined. The results also showed that after 100 h of milling time nanostructured α-Al (Mg, B) solid solution phase whose crystallite sizes are below 17 nm were obtained. Also, radiation shielding parameters have been investigated using NaI (Tl) γ-ray spectrometry at 662 and 1173 keV energies obtained via 137 Cs and 60 Co radioactive point sources. The obtained experimental data have been compared with XCOM theoretical data. The experimental data was utilized to calculate the half-value layer, tenth-value layer, and mean free path values. According to the obtained data, Al 50 Mg 25 B 25 alloy powder prepared and annealed at 300 °C has been shown to provide better protection against radiation.